2010
DOI: 10.1016/s1474-4422(10)70023-5
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive dexamethasone in bacterial meningitis: a meta-analysis of individual patient data

Abstract: SummaryBackgroundDexamethasone improves outcome for some patients with bacterial meningitis, but not others. We aimed to identify which patients are most likely to benefit from dexamethasone treatment.MethodsWe did a meta-analysis of individual patient data from the randomised, double-blind, placebo-controlled trials of dexamethasone for bacterial meningitis in patients of all ages for which raw data were available. The pre-determined outcome measures were death at the time of first follow-up, death or severe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
124
1
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 207 publications
(133 citation statements)
references
References 37 publications
1
124
1
7
Order By: Relevance
“…The use of dexamethasone in bacterial meningitis has been proven effective in patients in high‐income countries with S. pneumoniae meningitis 14; however, no effect has been established in patients with L. monocytogenes meningitis or in immunocompromised patients with human immunodeficiency virus infection 15. As RTR were found to have a different spectrum of causative microorganisms, it is unclear whether adjunctive dexamethasone has a role in the treatment of SOT patients.…”
Section: Discussionmentioning
confidence: 99%
“…The use of dexamethasone in bacterial meningitis has been proven effective in patients in high‐income countries with S. pneumoniae meningitis 14; however, no effect has been established in patients with L. monocytogenes meningitis or in immunocompromised patients with human immunodeficiency virus infection 15. As RTR were found to have a different spectrum of causative microorganisms, it is unclear whether adjunctive dexamethasone has a role in the treatment of SOT patients.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, one cannot rule-out this disagreement as a potential source of discrepancy between the current and published results, although it does not seem likely that it could completely account for it (6,7). First, two recent meta-analyses of placebo-controlled trials demonstrated that commencing dexamethasone before (or with) the first antibiotic dose or after antibiotic treatment had already started had no impact on its effects (8,9). In the present analysis, dexamethasone had no effect on mortality or full recovery in the entire cohort, but also in the subgroup of patients who received antibiotics before dexamethasone, as well as in the subgroup in which dexamethasone was started immediately before or with the first antibiotic dose.…”
Section: Antibiotic Treatment and Dexamethasone Regimenmentioning
confidence: 99%
“…This particular schedule was recently reported to apparently improve the outcomes of pneumococcal diseases in daily practice in a developed European country (7). On the other hand, recent meta-analyses of placebo-controlled trails indicate that the effect of early dexamethasone in adults is seemingly less robust than theoretically expected, and might be affected by trial quality, socio-economic level of the country (reflecting on access to medical care, HIV infection prevalence and treatment possibilities, but probably also on other factors), causative agent and level of evidence of bacterial infection (5,(8)(9)(10). Overall, the survival benefit is uncertain, although some benefit might be confined to the patients with pneumococcal meningitis in high-income countries (5,(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations